Spectrum allocation method for cognitive satellite network based on service priorities - Min JIA; Xiaoye JING; Xiaofeng LIU; Feng LIU; Qing GUO; Xuemai GU (Tongxin xuebao)
By using spectrum allocation technology of cognitive radio into integrated satellite and terrestrial networks,the satellite communication network can share spectrum with the terrestrial network and improve utilization efficiency of frequency spectrum in the satellite communication system.Firstly,a spectrum resource sharing model in integrated satellite and terrestrial networks was introduced,and the scenery that cognitive satellite downlinks use the vacant spectrum of terrestrial network was analyzed.Then,the interference and signal model was analyzed.Finally,considering different priority types of satellite terrestrial terminals,a spectrum allocation scheme based on priority was proposed,which could ensure the total throughput in satellite downlink communication and increase the throughput of high-priority terrestrial terminals.